Muslim Consumers' Perceptions of The Boycott of Israeli Products - Ayuprasadani, Aisyah Amalia; Ardhany, Ayu Kusuma; Ulum, Misbahul; Alicia Aulia Putri; Saifuddin Zuhri (ARRUS Journal of Social Sciences and Humanities, 2024)
This article discusses Muslim consumers' perceptions of the boycott of Israeli products. The boycott of Israeli products is a significant global issue, particularly for Muslim consumers. This boycott is a form of global protest Israel's military invasion of the Palestinian people. This protest movement is commonly known as the Boycott, Divestment, and Sanctions (BDS) campaign. In line with this, the Indonesian Council of Ulama (MUI) has issued a halal fatwa regarding products affiliated with Israel. According to MUI Fatwa No. 83 of 2023 on the Legal Status of Supporting the Palestinian Struggle, it is deemed forbidden (haram) to support Israel's aggression against Palestine, while supporting Palestine's struggle is considered obligatory. This research aims to understand Muslim consumers' perceptions of the boycott of Israeli products. In addition to surveys, literature reviews were conducted to identify the factors influencing consumer decisions. The findings of the study indicate that Muslim consumers tend to avoid Israeli products produced in occupied territories or those known to support Israeli government policies. Muslim consumer purchasing decisions are influenced by the following factors: cultural factors, social factors, personal factors, and psychological factors.